Construction of lumped-parameter cardiovascular models using the CellML language. (3rd October 2018) - Shi, Yubing; Lawford, Patricia; Hose, D. Rodney
Abstract: Lumped-parameter models are widely used by cardiovascular researchers in the analysis of the circulatory dynamics. However, portability and model exchange have always been a problem, with different researchers implement the model differently. To improve the situation, in this study, a group of lumped-parameter cardiovascular system models with different levels of complexity have been implemented using the CellML mark-up language. The models have been curated and made publicly available in the CellML model repository, and the purpose of this paper is to provide further technical details to support the usage of these models by the research community. The developed models are validated and tested under the OpenCell environment as part of the curation process. Simulation results agree well with typical published data on cardiovascular system response.